PERFORMANCE ANALYSIS OF FEMALE EMPLOYEES IN EFFORTS TO IMPROVE GENDER ADMINISTRATION IN THE TECHNICAL IMPLEMENTING UNIT OF BEKRI LAMPUNG CENTRAL DEPARTMENT OF WATERING SERVICE - Muhammad Fikri Akbar (Saburai International Journal of Social Sciences and Development, 2021)
Abstract. This study aims to determine the extent of the performance of female employees in the Service Technical Implementation Unit. Irrigation of Bekri, Central Lampung district in terms of field activities to improve gender mainstreaming. According to the method, this research is classified as a descriptive research design with a descriptive qualitative design. The researcher intends to explain and explain the obstacles that exist in the field activities of the Bekri Irrigation Agency Technical Implementation Unit related to the performance of female employees and efforts to improve gender mainstreaming in the Implementing Unit. Bekri Irrigation Service technicalities in 2019. The subjects in this study were female employees in the Bekri Irrigation Service Technical Implementation Unit itself. The data collection method is by observation and interview, documentation, and literature study. For the data validity checking technique, this research uses the triangulation technique, while the data analysis is through the stages of data reduction, data presentation, and conclusion drawing. The results of this study were the finding of job gaps between male and female employees in the field activities of the Bekri Irrigation Agency Technical Implementation Unit. Female employees of the Bekri Irrigation Service's Technical Implementing Unit have never been directly involved in field activities of the Bekri Irrigation Service's Technical Implementing Unit. The Head of the Bekri Irrigation Service Technical Implementation Unit considers that the work in the field is heavy and has high risk so that he considers female employees to be unable to carry out technical duties so that female employee in the Bekri Irrigation Service Technical Implementation Unit is only assigned to office administrative matters. Whereas the aim of holding gender mainstreaming itself is to eliminate and eliminate gender issues and work disparities in the irrigation sector in the activities of the Bekri Irrigation Service Technical Implementing Unit. The conclusion of this research is the performance of female employees of the Technical Implementation Unit of the Bekri Central Lampung Irrigation Service in terms of completing office administration and staffing work well, being quite punctual in the process, and able to carry out their duties with full responsibility but for the technical field, female employees in the Implementing Unit Bekri Irrigation Agency technical is blind about the work in the field Keywords: performance, female employees, gender mainstreaming